Стилізація відео за допомогою візуальних ефектів - Котельніков, І. В.; Грицаков, І. В. (ХНУРЕ, 2024)
Stylization of a video sequence is the art of choosing and creating an aesthetic image that complements the plot, mood and perception of the audience. Stylizing a video sequence involves many aspects, such as color selection, framing, lighting, motion effects, and visual elements. Each of these elements can be used to create a certain mood or convey certain information.
Keywords: стилізація відео; візуальний ефект